Enhancing Support for Adolescent Pregnant Mothers: A Comparative Study of the Continuity of Midwifery Care (CoMC) Model and Maternal and Child Health (MCH) Book - Susanti, Dewi; Hardisman, Hardisman; Yusrawati; Mudjiran (STIKes Alifah Padang, 2023)
Adolescent pregnancy, especially in low- and middle-income countries, is a global concern with significant health implications for both mothers and infants. This research compares the effectiveness of two interventions, the Continuity of Midwifery Care (CoMC) model and the Maternal and Child Health (MCH) Book, in enhancing family and spousal support for adolescent pregnant mothers. Using a quantitative approach with a quasi-experimental design, the study is conducted in Padang City over four months, involving 20 Independent Midwife Practices (IMP). Purposive sampling is employed based on specific criteria. Data collection utilizes questionnaires measuring family and spousal support in emotional, appreciation, instrumental, and informational dimensions, which underwent validation and reliability testing. Preliminary results indicate that both interventions improve family and spousal support, with the CoMC model showing greater efficacy. Appreciation support, emotional support, instrumental support, and informational support play crucial roles in positively impacting adolescent pregnant mothers' well-being. The CoMC model excels in delivering personalized care, emphasizing emotional support, providing practical assistance, and offering timely and relevant information.In conclusion, this study underscores the importance of family and spousal support in adolescent pregnancies and highlights the effectiveness of both interventions. The CoMC model stands out as a more comprehensive and personalized approach. Implementing this model in healthcare policies can significantly enhance care quality for pregnant adolescents, fostering a supportive environment for both mothers and infants.